Budesonide nebulization in preterm neonates with evolving brochopulmonary dysplasia after 14 days of life: a case series - Sivarama, Subhodh S.; Ashokraja, J.; Muthukumaran, N. (International Journal of Contemporary Pediatrics, 2021)
Bronchopulmonary dysplasia (BPD) with oxygen dependence at 36 weeks postmenstrual age (PMA), remains an important complication of premature newborns. BPD occurs due to pulmonary inflammation. Reducing pulmonary inﬂammation with postnatal systemic corticosteroids reduces the incidence of BPD but is associated with an increased risk of long and short-term side effects. Local administration of corticosteroids via inhalation might be an effective and safe alternative. Currently, there is no recommendation for use of inhaled corticosteroids in neonatal respiratory care. However, it is being used in neonatal intensive care units (NICU) across the world in ventilator and oxygen-dependent babies. We shared our experience with the use of inhaled budesonide on nine ventilator-dependent very low birth weight (VLBW) preterm neonates in the form of case series and review the literature.